Posttest Only Evaluation of Garlic Extract as Aedes aegypti Larvicide - Tjitrowati Djaafar; Amsal Amsal; A Bungawati; Gusman Gusman; Saharudin Saharudin (Poltekkes Kemenkes Palu, 2026)
Background: Dengue remains an important Aedes-borne disease, and Aedes aegypti is the primary vector in many endemic settings. The expansion of dengue risk, increasing insecticide resistance, and the need for environmentally acceptable vector-control options support the evaluation of plant-based larvicides. This study assessed the mortality of Aedes aegypti larvae exposed to garlic (Allium sativum) extract. Methods: A true laboratory experiment with a posttest-only control group design was conducted at the Entomology Laboratory, Department of Environmental Health, Poltekkes Kemenkes Palu, in September 2023. Third-instar Aedes aegypti larvae were allocated to six groups: control (0 ppm) and garlic extract concentrations of 0.8, 0.9, 1.0, 1.1, and 1.2 ppm. Each group had four replications with 20 larvae per container (n = 480). Mortality was observed after 2, 4, 6, 12, and 24 hours and analyzed descriptively. Results: No mortality occurred in the control group. Cumulative 24-hour mortality increased from 8/80 larvae (10.0%) at 0.8 ppm to 12/80 (15.0%) at 0.9 ppm, 13/80 (16.25%) at 1.0 ppm, 14/80 (17.5%) at 1.1 ppm, and 16/80 (20.0%) at 1.2 ppm. Conclusion: Garlic extract produced a concentration-related increase in Aedes aegypti larval mortality, but concentrations below 2 ppm did not produce immediate high-level larval control within 24 hours. These low-concentration findings support further studies on sublethal effects, including delayed larval development, impaired pupation, and reduced adult emergence, alongside broader concentration ranges, lethal concentration analyses, and standard positive-control comparisons